Relevance of the capital adequacy ratio, as a mediator of its contribution to return on assets empirical study on the conventional banking sector listed on the Indonesia Stock Exchange in 2018-2022 - Al Fauzi Hakim; Akhmadi Akhmadi; Wawan Ichwanudin (Trigin Publisher, 2023)
Banking is an institution that has a crucial role in stimulating the economy. This study aims to develop a research model to address the business phenomenon and research gap between loan-deposit to ratio on Return on Asset with capital adequacy ratio as a mediating variable. The method used by the author in this research is a descriptive quantitative method with an associative approach. The population in this study was 47 conventional banks listed on the Indonesia stock exchange; the sample in this study was 13 banking companies, according to the research variables concerning public financial reports from 2018-2022. Sampling techniques with purposive sampling were used. Data analysis techniques with regression and path analysis using the sobelt test. The results showed that loan deposit to ratio has a significant effect on return on assets, loan deposit to ratio has a significant impact on capital adequacy ratio, loan deposit to ratio has a significant effect on return on investments, capital adequacy ratio can mediate the impact of loan deposit to ratio on return on assets. In addition, the authors hope this research can make a theoretical contribution to the financial management and banking literature in this context.